2015
DOI: 10.1002/ajpa.22804
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive value of secondary males in the polygynous multi‐level society of hamadryas baboons

Abstract: Hamadryas follower males enabled leaders to retain females for longer periods of time-likely through unit defense, social relationships with OMU members, and/or infant protection. Hamadryas leaders appear to be able to monopolize access to females despite the presence of followers, and as such any enhanced reproduction derived from the presence of followers likely increases the fitness of the leader rather than the follower. Thus the relationship between leaders and followers in hamadryas society appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 98 publications
1
45
1
Order By: Relevance
“…Females are spatially segregated from other OMUs, partly through male enforcement (Kummer, ; Swedell & Schreier, ). Despite their name, some OMUs may have “follower males” (Chowdhury, Pines, Saunders, & Swedell, ; Kummer, ; Pines, Saunders, & Swedell, ), who are less likely to interact sexually with females than leader males (Swedell, ). Multiple OMUs aggregate into clans, and several clans and additional bachelor males form a band (Kummer, ; Swedell & Plummer, ).…”
Section: Baboons As a Model For Social Evolutionmentioning
confidence: 99%
“…Females are spatially segregated from other OMUs, partly through male enforcement (Kummer, ; Swedell & Schreier, ). Despite their name, some OMUs may have “follower males” (Chowdhury, Pines, Saunders, & Swedell, ; Kummer, ; Pines, Saunders, & Swedell, ), who are less likely to interact sexually with females than leader males (Swedell, ). Multiple OMUs aggregate into clans, and several clans and additional bachelor males form a band (Kummer, ; Swedell & Plummer, ).…”
Section: Baboons As a Model For Social Evolutionmentioning
confidence: 99%
“…Few studies have addressed this topic in other species with both one‐male and multimale groups. In both hamadryas and gelada baboons, the presence of follower males led to longer tenures, more females per group, and increased reproductive success for the dominant male and also provided benefits for the followers . In contrast, Port et al found no benefits for dominant male Verreaux's sifakas to have followers, but those followers have higher fitness than males that do not join groups (floaters).…”
Section: Fitness Consequences Of Male Dispersalmentioning
confidence: 97%
“…In both hamadryas and gelada baboons, the presence of follower males led to longer tenures, more females per group, and increased reproductive success for the dominant male and also provided benefits for the followers. 16,81 In contrast, Port et al 14 National Park, Gabon, 89 ) or human barriers (i.e., Grauer's gorillas in the highland sector of Kahuzi-Beiga is only~100 km 2 ), multimale groups rarely occur. 35 The possibility that human disturbance has had an influence on grouping patterns in mountain gorillas cannot be ruled out, but there is also no practical way to test the hypothesis.…”
Section: Subordinate Males: Stay or Go?mentioning
confidence: 99%
“…We do not know the strategy behind the takeovers for enough dyads of known kinship to test whether followers that are related to leaders are more likely to inherit adult females than unrelated followers. Nevertheless, it has recently been shown that OMUs with one or more followers produce three times as many offspring as OMUs without followers due to prolonged leader and female tenures and the acquisition by leaders of twice as many females during their tenure [Chowdhury et al, ]. Thus, assuming, as behavioral evidence suggests, near exclusive paternity certainty for leader males, the presence of followers appears to increase a leader's direct fitness and consequentially a related follower's indirect fitness [Chowdhury et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Follower males apparently benefit from their status as followers in that they often acquire more of their leader's females than other males [Pines et al, , ]. Leader males also benefit from follower presence, which is associated with longer leader tenure lengths, more females, and higher reproductive output based on observational data [Chowdhury et al, ]. If followers and leaders are kin, then both could also benefit via inclusive fitness [Abegglen, ; Chowdhury et al, ; Colmenares, ; Pines et al, ].…”
Section: Introductionmentioning
confidence: 99%